2022
DOI: 10.1038/s42003-022-04079-0
|View full text |Cite
|
Sign up to set email alerts
|

Fossil bone histology reveals ancient origins for rapid juvenile growth in tetrapods

Abstract: Patterns of growth throughout the lifetime of an animal reflect critical life history traits such as reproductive timing, physiology, and ecological interactions. The ancestral growth pattern for tetrapods has traditionally been described as slow-to-moderately paced, akin to modern amphibians, with fast growth and high metabolic rates considered a specialized physiological trait of amniotes. Here, we present bone histology from an ontogenetic series of the Early Carboniferous stem tetrapod Whatcheeria deltae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…This tetrapodomorph, which lived during the Carboniferous Period, was inferred as being ectothermic in our study, based on canal size. However, it displays FLC in its femoral cross section, 44 a type of tissue frequently used as evidence for endothermy by numerous studies, including Grigg et al. 4 However, † Whatcheeria ’s HMC is in accordance with big erythrocytes, suggesting its cardiovascular system did not attain a sufficient efficiency to sustain tachymetabolism ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This tetrapodomorph, which lived during the Carboniferous Period, was inferred as being ectothermic in our study, based on canal size. However, it displays FLC in its femoral cross section, 44 a type of tissue frequently used as evidence for endothermy by numerous studies, including Grigg et al. 4 However, † Whatcheeria ’s HMC is in accordance with big erythrocytes, suggesting its cardiovascular system did not attain a sufficient efficiency to sustain tachymetabolism ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dry bone lesions have shown promising results in differentiating between some tumour types. Immunohistochemistry and molecular analysis methods have provided insights into ancient tumours' cellular and molecular characteristics [36]. Although a powerful tool in paleo-oncology, this technique does have its limitations.…”
Section: Technological and Methodological Advances In The Detection O...mentioning
confidence: 99%